Liquid rolling of woven carbon fibers reinforced Al5083-matrix composites. (5th April 2016) - Zhang, Junjia; Liu, Shichao; Lu, Yiping; Yin, Xuelin; Zhang, Yubo; Li, Tingju
Abstract: A liquid rolling method was successfully developed for the fabrication of woven carbon fibers reinforced Al5083-matrix composites. The woven fibers were coated with Ni/P to facilitate wetting of the fibers by the molten matrix. It was found that the composite fabricated in this way had a good microstructure with few defects, which was most likely due to the occurrences of pressure infiltration, rapid solidification, and hot-deformation strengthening on the materials. Finite-element simulation was conducted to analyze the temperature field and solidification process during the liquid rolling. A wide semi-solid region was observed in the simulation, and it would effectively avoid the fiber damages. The results of three-point bending measurements implied that the application of liquid rolling and the addition of reinforcements could both offer obvious improvements to the materials. The liquid rolling method could increase the matrix bending strength by 43% than the casting method. Furthermore, when the liquid rolling was used, the addition of woven fibers could offer an improvement of 22% to the matrix. Graphical abstract: Highlights: A liquid rolling method is developed for fabrication of woven carbon fibers reinforced Al-matrix composites. This process is simple in equipment, high in efficiency, and potential to be scaled up for further continuous productions. The liquid rolling method could increase the matrix bending strength by 43% than the casting method. When the liquid rolling was used, the addition of woven fibers could offer an improvement by 22% to the matrix.